SISTEM MANAJEMEN KINERJA BERBASIS PADA INPUT (INDIVIDU GURU) PROSES DAN OUTPUT - Mesiono, Mesiono; Harahap, Hotni Sari (FKIP Universitas Al Washliyah Medan, 2024)
An effective performance management system is key to improving the quality of education and student learning outcomes. This article discusses performance management systems based on input (individual teacher), processes, and outputs in three schools that have implemented this method. Data is collected through in-depth interviews, live observations, and analysis of school policy documents and teacher performance reports. Research results show that there is a strong relationship between individual teacher competence and skills (inputs), implementation and monitoring of teaching (processes), and results and impact on performance. (output). Teachers who received constructive feedback and followed a continuous training program showed significant performance improvements. In addition, appreciation and recognition of good performance increases the motivation and satisfaction of teachers. Recommendations included clear objectives, regular feedback, sustained training programmes, and a fair and transparent system of awards and recognitions. In conclusion, the implementation of a comprehensive and sustainable performance management system can improve the performance of individual teachers and schools as a whole, as well as help competitive advantage in the world of education.